KAJIAN PENGARUH PROMOSI, ADVERTISING DAN EXPERIENTAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN KARTU BERMAIN DI PT. TRANSREKREASINDO TRANSSTUDIO MINI JEMBER - Yani Dahliani; Haifa Haifa; Rivaldi Rendrahadi (Sekolah Tinggi Pariwisata Mataram, 2020)
This study aims: (1) to find out promotion, advertising and experiential marketing simultaneously influence the purchase decision at PT. Transrekreasindo Transstudio Mini Jember. (2) to find out promotion, advertising and experiential marketing partial effect on purchasing decisions at PT. Transrekreasindo Transstudio Mini Jember. In this study researchers used primary data. Primary data in this study were obtained by conducting interviews by giving questionnaires. Researchers took a sample of 50 respondents using the total sampling method. The analysis techniques used include validity and reliability, classic assumption tests (normality test, multicollinearity test, hetoroscedasticity test), multiple linear regression analysis, coefficient of determination (R2), and hypothesis testing (F test and t test). From the results of the study show that promotion, advertising and experiential marketing simultaneously influence the purchase decision.